2018
DOI: 10.1002/adsu.201800066
|View full text |Cite
|
Sign up to set email alerts
|

Control of Transmittance by Thermally Induced Phase Transition in Guest–Host Liquid Crystals

Abstract: Guest-host liquid crystal (GHLC) consists of host liquid crystal and guest dichroic dye. It can be switched between the transparent and opaque states by controlling the light absorption. In this paper, transmission control via the phase transition in GHLCs is presented. The smectic A, nematic, and isotropic phases as the high-, mid-, and low-transmittance states of a GHLC cell are used, respectively, to control the transmittance. It is demonstrated that the proposed GHLC cell can be used as a self-shading smar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Liquid crystal 8CB (4 -Octyl-4-biphenylcarbonitrile) was purchased from Synthon (Bitterfeld-Wolfen, Germany), Dye 1 (a coumarin derivative) was purchased from a commercial source, Dye 2 was synthesized according to the literature [24]; these three materials are depicted in Figure 1a. Recent work by Oh et al [5] has shown that the transmission of a smart window can be thermally controlled using a dichroic dye in a liquid crystal (LC). Three different LC phases (i.e., smectic, nematic and isotropic) were used to create high-, mid-and low-transmitting states.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liquid crystal 8CB (4 -Octyl-4-biphenylcarbonitrile) was purchased from Synthon (Bitterfeld-Wolfen, Germany), Dye 1 (a coumarin derivative) was purchased from a commercial source, Dye 2 was synthesized according to the literature [24]; these three materials are depicted in Figure 1a. Recent work by Oh et al [5] has shown that the transmission of a smart window can be thermally controlled using a dichroic dye in a liquid crystal (LC). Three different LC phases (i.e., smectic, nematic and isotropic) were used to create high-, mid-and low-transmitting states.…”
Section: Methodsmentioning
confidence: 99%
“…The built environment is a large consumer of electricity, with 76% being spent in residential and commercial buildings [1], around half of this on electricity for heating/cooling and lighting [2]. One way to reduce the amount of energy spent on heating and cooling is by controlling the amount of incoming sunlight using "smart windows" [3,4] which can change their transmissivity in response to stimuli, including heat [5][6][7], electricity [4,8,9] and light [10][11][12]. In addition, using excess sunlight to generate electricity can even result in energy-generating windows [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed, it is necessary to absorb (or transmit) the sunlight incident at a higher (or lower) elevation angle in summer (or winter) to save energy. GHLC devices, comprising a host LC and guest dichroic dye, have attracted considerable attention owing to their high transmittance in a transparent state and polarizer-free structure [32][33][34][35][36][37][38][39][40][41]. Due to their dichroism, dye molecules strongly (or weakly) absorb the light that is polarized parallel (or perpendicular) to their absorption axis (Figure 2a).…”
Section: Design Principles Of the Devicementioning
confidence: 99%
“…Switchable properties that are of particular interest are changes in color, transparency, scattering, and/or reflectivity. [19,20] Potential stimuli of interest as triggers include electrical, [20][21][22] thermal, [23][24][25] and optical, [26][27][28] although there are many other options. [17,29,30] A potential deployment that has not been exploited for such "smart" systems is signage.…”
Section: Introductionmentioning
confidence: 99%